2020
DOI: 10.1183/13993003.02250-2020
|View full text |Cite
|
Sign up to set email alerts
|

High rifampicin-resistant TB cure rates and prevention of severe ototoxicity after replacing the injectable by linezolid in early stage of hearing loss

Abstract: The short treatment regimen (STR) achieves over 80% cure in rifampicin-resistant tuberculosis (RR-TB) patients. However, ototoxicity induced by the injectable is a concern. This is the first study to evaluate the replacement of injectables by linezolid in patients with audiometry abnormalities at baseline or during the treatment.We conducted a retrospective cohort study of all RR-TB patients started on the STR between 2016 - June 2019 in Niger. Patients underwent audiometry every 2 months in 2016, and every mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 19 publications
1
19
0
Order By: Relevance
“…Without core drug regimens are little effective. [8] On the other hand, in Niger linezolid was effectively used as companion drug in patients with fluoroquinolone-susceptible RR-TB and a contraindication for treatment with second-line injectable drugs [13] Our sample size was too small to conclude whether relapse-free cure was significantly higher with 95% certainty for the BDQ-STR compared to the LZD/GFX-STR. However, data on culture conversion showed that the BDQ-STR had an earlier killing effect than the LZD/GFX-STR in a cohort mainly consisting of patients with fluoroquinolone-resistant cohort.…”
Section: To the Editormentioning
confidence: 88%
See 1 more Smart Citation
“…Without core drug regimens are little effective. [8] On the other hand, in Niger linezolid was effectively used as companion drug in patients with fluoroquinolone-susceptible RR-TB and a contraindication for treatment with second-line injectable drugs [13] Our sample size was too small to conclude whether relapse-free cure was significantly higher with 95% certainty for the BDQ-STR compared to the LZD/GFX-STR. However, data on culture conversion showed that the BDQ-STR had an earlier killing effect than the LZD/GFX-STR in a cohort mainly consisting of patients with fluoroquinolone-resistant cohort.…”
Section: To the Editormentioning
confidence: 88%
“…Without core drugs, regimens are less effective [ 8 ]. On the other hand, in Niger linezolid was effectively used as companion drug in patients with fluoroquinolone-susceptible RR-TB and a contraindication for treatment with second-line injectable drugs [ 13 ].…”
mentioning
confidence: 99%
“…The study setting and procedures are published elsewhere. 4,7 The 9-11 mo STR was the standard treatment regimen and included a FQ (moxifloxacin or gatifloxacin), clofazimine, ethambutol and pyrazinamide throughout, supplemented by kanamycin, prothionamide and high-dose isoniazid (10 mg/kg) during the first 4 mo (6 mo if conversion to smear microscopy was delayed). Since 2017, the second-line injectable kanamycin has been replaced by linezolid in case of any hearing disturbance on audiometry.…”
Section: Methodsmentioning
confidence: 99%
“…Since 2017, the second-line injectable kanamycin has been replaced by linezolid in case of any hearing disturbance on audiometry. 7 In case of failure or relapse, patients started a BDQ-regimen, including bedaquiline throughout treatment and, depending on drug susceptibility testing (DST) results, linezolid with either a second-line injectable or delamanid. The STR structure was respected.…”
Section: Methodsmentioning
confidence: 99%
“…The presence of drug resistance is associated with poor treatment management. In 2020, the World Health Organization (WHO) reported 465,000 cases of rifampicin-resistant tuberculosis (RR-TB) with treatment success rates of 57% [ 1 ]. The combination of second-line anti-TB drugs to treat drug-resistant tuberculosis (DR-TB) is more toxic and leads to adverse effects.…”
Section: Introductionmentioning
confidence: 99%